Media Sosial sebagai Arena Diskusi Keberagamaan: Analisis Komentar Netizen tentang Hijab di Instagram - Tauhida, Dini; Busro, Busro; Supriyadi, Yogi (Tatar Pasundan: Jurnal Diklat Keagamaan, 2024)
This study aims to analyze netizen responses on Instagram to Rina Nose's decision to remove her hijab. Drawing on the secularism theory developed by Jose Casanova, which highlights three different connotations of secularism, the research seeks to explore netizen response patterns, identify key themes that emerge from the comments, and examine how social media platforms, particularly Instagram, have become a significant arena for public discussion and debate on religious issues. Employing a qualitative approach, data were collected from comments posted on Rina Nose's Instagram account (@rinanose16) using the ExportComment application and analyzed with Microsoft Excel. The comments were categorized into five main groups: praise, criticism, support, rejection, and rebuttal. The findings reveal a diverse range of responses, with a relatively even distribution across the categories of support, criticism, rejection, praise, and rebuttal. These results reflect the complexity of Indonesian society’s views on religious issues and personal identity in the digital era. The study provides valuable insights into how social media, especially Instagram, serves as an essential space for public debate on socio-religious matters. Furthermore, the study can serve as a foundation for future research on the role of social media in shaping public opinion and expressing religious perspectives. As one of the first studies to specifically analyze netizen reactions on Instagram to a public figure's decision to remove the hijab, this research makes an important contribution to the literature on religion and social media in Indonesia. Keywords: Hijab; Instagram; Social Media; Netizen; Sosio-Religius